Econophysics of the Kolkata Restaurant problem and related games : classical and quantum strategies for multi-agent, multi-choice repetitive games /: classical and quantum strategies for multi-agent, multi-choice repetitive games. (2017) - Chakrabarti, B. K (Bikas K.), 1952-; Chatterjee, Arnab; Ghosh, Asim; Mukherjee, Sudip; Tamir, Boaz
No abstract available